The IOS Annual Volume 23: "Drought Will Drive You Even Toward Your Foe" - Cerqueglini, Letizia; Cohen, Yoram; Gilan, Amir; Sheyhatovitch, Beata; Wasserman, Nathan (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
The IOS Annual volume 23: "Drought Will Drive You Even Toward Your Foe" brings forth studies devoted to a wide array fields and disciplines of the Middle East. The two sections - Ancient Near East and Semitics include six articles. The Ancient Near East contains three articles dealing with the history of Mesopotamia and ancient Syria (Steinkeller; Steinmayer; Cohen), and the second and concluding part of "On Aramaic Loanwords in Neo- and Late Babylonian Texts" (Zadok), which appeared in IOS 21. The Semitic section includes two articles. The first is about metaphors in the Bedouins' Poetry (Cerqueglini). The second is a study of the vocalization of guttural consonants in the Secunda (Maurizio)